Pengaruh Inflasi Dan Tingkat Suku Bunga Bank Indonesia (BI) Terhadap Profitabilitas Bank Sumut Kantor Cabang Pembantu Syariah Karya Medan Tahun 2017-2021 - M. Fauzi Aulia; Muhammad Arif (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This research is entitled "The Influence of Inflation and Bank Indonesia (BI) Interest Rates on the Profitability of North Sumatra Bank Karya Medan Syariah Sub-Branch Office in 2017-2021". The purpose of this study was to determine the effect of inflation on the profitability of the North Sumatran bank's sharia sub-branch office Karya Medan in 2017-2021, the influence of interest rates on the profitability of the North Sumatra bank's sharia sub-branch office Karya Medan in 2017-2021 and the effect of inflation and interest rates simultaneously on the profitability of North Sumatran banks. sharia sub-branch office Karya Medan in 2017-2021. The research method used in this study is a qualitative descriptive method with primary and secondary data. The research results obtained are interest rates and inflation simultaneously have a significant effect on profitability as measured by Return on Assets (ROA).